Liquid-liquid equilibrium and partitioning features of bovine trypsin in Ucon 50 HB5100 /sodium citrate aqueous two phase systems - Tubío, Gisela (2008)
The phase diagrams of Ucon 50-HB-5100, a non-ionic random copolymer of ethylene oxide and propylene oxide (EOPO) and sodium citrate aqueous two-phase systems were determined at different pHs (5.20 and 8.20) and temperatures (5, 20 and 40º C). The binodal curves were determined by refractive index and enzymatic assay of the solution and described using a four-parameter sigmoidal equation, the reliability of the measured tie line compositions was ascertained by correlation equations given by Othmer Tobias and Bancroft. The two-phase area was expanded by increasing both pH and temperature. The partitioning of bovine trypsin and a-chymotrypsin, proteases of similar physico-chemical properties was investigated in order to evaluate the applicability of partitioning as a putative method to isolate from pancreas and to obtain any information about their partitioning mechanism. The effect of different factors such as pH, tie line length and the presence of an inorganic salt on the protein partition coefficient were analyzed.